Fathers' Postnatal Mental Health and Child Well-Being at Age Five: The Mediating Role of Parenting Behavior. (September 2014) - Giallo, Rebecca; Cooklin, Amanda; Wade, Catherine; D'Esposito, Fabrizio; Nicholson, Jan M.
Fathers' postnatal mental health is associated with emotional and behavioral outcomes for children in early childhood. The aim of this study was to examine whether parenting behavior mediated the relationship between fathers' postnatal psychological distress and emotional–behavioral outcomes for children at age 5. The sample consisted of 2, 025 fathers participating in Growing Up In Australia: The Longitudinal Study of Australian Children. Data collected when the children were aged 0 to 12 months and 4 to 5 years were used. Results revealed that the relationship between fathers' postnatal distress and children's outcomes was mediated by parenting hostility (angry and frustrated reactions toward the child such as yelling), and this remained significant after controlling for fathers' concurrent mental health and mothers' postnatal mental health. These findings underscore the important contribution of fathers' postnatal mental health to later parenting behavior and child outcomes. Implications for policy and practice focused on improving mental health and parenting support to fathers in the early childhood period is discussed.